Characterization of Toxicity, Porosity, and Moisture Content of Bovine Freeze-dried Amnion and Bovine Amnion Sponge - Dwiyanto Oktavia; Heri Suroto; Teddy Heri Wardhana; Gilson Khang (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Amnion has potential roles as a biological dressing on an extensive wound defect and in tendon healing. Before clinical trials, the safety and compatibility level of bovine amnion is needed to be measured. This study aims to explain the toxicity, porosity, and moisture content characteristic of a bovine freeze-dried amnion membrane (FD-AM) and bovine amnion sponge. Methods: This study design was a randomized posttest only that quantifies the effect on the two groups of subjects. The samples were scaffolds from a bovine FD-AM and bovine amnion sponge. The toxicity level was measured by MTT assay. Scanning electron microscope was conducted to measure porosity. Moisture content measurement was also done on both groups. The quantitative measurement of the moisture content and toxicity was conducted using descriptive statistic analysis. Results: In both groups, no toxicity was found based on the results, with an average value of 3.122 in the membrane group. The bovine amnion sponge group had a higher porosity and wider cavities, thereby increasing compatibility for cell proliferation. The sponge group had higher moisture content with a ratio of 10.559% and 7.776% compared to membrane groups. Conclusion: Bovine FD-AM and bovine amnion sponge have good safety levels. A bovine amnion sponge is more suitable for cell proliferation due to better porosity and wider cavity. Further study is needed regarding the preservation ability of bovine amnion sponge due to moisture content levels higher than 10%.